Entrepreneurship Education as a Driver for Economic Recovery in the Post-Pandemic Era - Dzingirai, Mufaro; Ndava, Rodgers (IGI Global, 2022)
Entrepreneurship appears to be a lucrative career in the post-COVID-19 era given the scaling down of big companies owing to the negative effects of the COVID-19 pandemic. Although much has been said and written on the role of entrepreneurship in economic development and growth, scant is known about its role in economic recovery from crises. Therefore, this chapter aims to investigate how entrepreneurship education can act as a catalyst for economic recovery in the post-COVID-19 pandemic era. It was observed that entrepreneurship plays a catalyst role in promoting economic recovery through producing enterprising graduates and promoting divergent thinking in solving wicked problems in the post-pandemic era. Nonetheless, it was also observed that the theoretical approach of teaching entrepreneurship was dominant at the expense of the practical approach due to limited resources. The outcomes of this study help practitioners and policymakers in making evidence-informed decisions.